ECB's evolving communication and policy preferences since 2021 strategy review - Markus Haavio; Joni Heikkinen; Pirkka Jalasjoki; Juha Kilponen; Maritta Paloviita (Bank of Finland, 2025)
We study the evolution of the European Central Bank's (ECB) monetary policy since July 2021, following the adoption of a new strategy and amid a period of volatile inflation. Utilizing text analysis, we assess changes in the general sentiment of the ECB's communication. Additionally, we employ topic modeling to develop an inflation focused tone index. By integrating these tone indices with real-time data from monetary policy meetings, we directly estimate the ECB's loss function. Our findings indicate a recent shift towards a more inflation-centered communication approach by the ECB. Preliminary results also suggest that the ECB's policy preferences have become more symmetric since July 2021.
urn:nbn:fi-fe2025031217129
Keywords: E31; E52; E58; 330; asymmetric loss function; central bank communication; textual analysis; topic model; optimal monetary policy